Synthesis of biaryl-linked cyclic peptoids. Issue 10 (8th March 2017) - Webster, Alexandra M.; Cobb, Steven L.
Graphical abstract: Highlights: Synthesis of MIDA boronate-containing linear peptoids. On resin Suzuki cross-coupling of linear peptoids. Preparation of novel biaryl-linked cyclic peptoids. Abstract: Peptoids, a class of peptidomimetic, have gained considerable attention as potential therapeutic agents due to properties such as biocompatibility and resistance to enzymatic degradation. In linear peptoids, conformational heterogeneity can arise due to cis/trans isomerization around the backbone tertiary amide bond which has led to an increasing interest in cyclic peptoids. Biaryl linkages appear as a common structural motif in many synthetic and naturally occurring cyclic peptides but they are yet to be utilized in the formation of cyclic peptoids. Herein, we describe the application of a solid-phase Suzuki cross-coupling strategy as a means to prepare of a series of biaryl-linked cyclic peptoids. The methodology presented allows access to a range of novel biaryl containing cyclic peptoids with varying ring sizes.